Fish Biodiversity as Ecological Support for False Gharial (Tomistoma schlegelii) Habitats in Tropical Rivers - Itra Hariyadi; Thira Rodchevid; Josyline Kendi (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This study aimed to analyze fish biodiversity and evaluate physicochemical water conditions supporting fish communities and the habitat sustainability of the false gharial (Tomistoma schlegelii) in a tropical freshwater river ecosystem. Methodology: This study used a purposive sampling method at three observation stations. Fish samples were collected using gill nets, fishing rods, traps, and traditional fishing gear. Water quality parameters were measured in situ using GPS, thermometer, pH meter, Secchi disk, stopwatch, and current-flow method, while dissolved oxygen and heavy metals were analyzed ex situ using Atomic Absorption Spectroscopy. Fish identification referred to Kottelat in 1993. Data were analyzed using Shannon–Wiener diversity index, evenness index, similarity index, dominance index, and Pearson correlation analysis with SPSS version 22. Main Findings: A total of 15 fish species were identified within the freshwater ecosystem. Fish diversity at all stations was categorized as moderate, with high evenness, high similarity, and low dominance values indicating relatively stable ecological conditions. Water temperature ranged from 28–29°C, dissolved oxygen from 6.4–6.8 mg/L, and pH remained at 6. Water transparency showed the strongest positive correlation with fish biodiversity (r² = 0.948), followed by dissolved oxygen and current velocity. Heavy metal concentrations remained below environmental quality standards. Novelty/Originality of this study: This study provides an integrated ecological assessment linking fish biodiversity, physicochemical water quality, and habitat suitability for the false gharial within a tropical freshwater ecosystem. This research highlights the ecological relationship between aquatic biodiversity and prey-resource availability supporting false gharial habitat sustainability.